Characterization of Two Novel Polyomaviruses of Birds by Using Multiply Primed Rolling-Circle Amplification of Their Genomes - Johne, Reimar (American Society for Microbiology, 2006)
Polyomaviruses are small nonenveloped particles with a circular double-stranded genome, approximately 5 kbp in size. The mammalian polyomaviruses mainly cause persistent subclinical infections in their natural nonimmunocompromised hosts. In contrast, the polyomaviruses of birds—avian polyomavirus (APV) and goose hemorrhagic polyomavirus (GHPV)—are the primary agents of acute and chronic disease with high mortality rates in young birds. Screening of field samples of diseased birds by consensus PCR revealed the presence of two novel polyomaviruses in the liver of an Eurasian bullfinch (Pyrrhula pyrrhula griseiventris) and in the spleen of a Eurasian jackdaw (Corvus monedula), tentatively designated as finch polyomavirus (FPyV) and crow polyomavirus (CPyV), respectively. The genomes of the viruses were amplified by using multiply primed rolling-circle amplification and cloned. Analysis of the FPyV and CPyV genome sequences revealed a close relationship to APV and GHPV, indicating the existence of a distinct avian group among the polyomaviruses. The main characteristics of this group are (i) involvement in fatal disease, (ii) the existence of an additional open reading frame in the 5′ region of the late mRNAs, and (iii) a different manner of DNA binding of the large tumor antigen compared to that of the mammalian polyomaviruses.